IMPROVING READING ABILITY THROUGH THE COMPETITIVE GAME ENGINEERING TECHNIQUES STORY FOR CLASS II STUDENTS OF BASIC SCHOOL - Sriwulan, Lussy; Mudrikah, Rika; Agra, Hana Sakura Putu (IKIP Siliwangi, 2018)
This research is motivated by the low reading ability of class II students at SDS 440 Ganesha. Through observation, it is known that the students' reading ability is low because students have low reminders so that students are less active in participating in learning. From the observations that have been made show that 63.6% (7 students) active in learning activities of all 11 students. Looking at the situation in the field, the researchers are interested in doing research with language play techniques complement the story, because language game techniques complement the story emphasizing real things students experience in everyday life. Reading skills through language game techniques completes the story is expected to trigger activity and creativity of students in the process of learning to read so that the teaching and learning process is not only dominated by the teacher. This classroom action research was carried out in two cycles, each cycle consisting of two meetings. In the first cycle the percentage of student learning completeness reached 63.6% (7 students), but was considered not to reach the target to be achieved, namely 90%. In the second cycle students' understanding has increased with student learning completeness reaching 90%.